2023
DOI: 10.1021/jacs.2c13823
|View full text |Cite
|
Sign up to set email alerts
|

[1,4]Diazocine-Embedded Electron-Rich Nanographenes with Cooperatively Dynamic Skeletons

Abstract: Curved nanographenes (NGs) are emerging as promising candidates for organic optoelectronics, supramolecular materials, and biological applications. Here we report a distinctive type of curved NGs bearing a [1,4]­diazocine core that is fused with four pentagonal rings. This is formed by Scholl-type cyclization of two adjacent carbazole moieties through an unusual diradical cation mechanism followed by C–H arylation. Owing to the strain in the unique 5–5–8–5–5-membered ring skeleton, the resulting NG adopts an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 58 publications
0
3
1
Order By: Relevance
“…Double saddle‐shaped structures were also observed for 2 , which were wider and deeper than that of 1 a (Figure 6a). Such C 2 ‐symmetric homochiral triple helicene was apparently different from the previously reported triple helicenes in which C 3 / D 3 ‐symmetry for homochiral conformers [27] and C 2 ‐symmetry for heterochiral structures [10g,14] were normally observed. The mean torsion angle of the inner rim (29.4°) of the diaza[7]helicene moiety was comparable with that of 1 a (30.1°).…”
Section: Resultscontrasting
confidence: 92%
See 2 more Smart Citations
“…Double saddle‐shaped structures were also observed for 2 , which were wider and deeper than that of 1 a (Figure 6a). Such C 2 ‐symmetric homochiral triple helicene was apparently different from the previously reported triple helicenes in which C 3 / D 3 ‐symmetry for homochiral conformers [27] and C 2 ‐symmetry for heterochiral structures [10g,14] were normally observed. The mean torsion angle of the inner rim (29.4°) of the diaza[7]helicene moiety was comparable with that of 1 a (30.1°).…”
Section: Resultscontrasting
confidence: 92%
“…Meanwhile, the incorporation of carbazole moieties would facilitate the simultaneous accomplishment of nitrogen‐doping, creation of polycyclic skeleton, and provision of reactive sites. However, practical attempts showed that the octagonal cyclization of the two carbazole moieties was preferred over the heptagonal cyclization of the adjacent phenyl and carbazole moieties under Scholl reaction condition (Scheme S1) [14] . Thus, we switched to a non‐oxidative cyclization route involving the Pd‐catalyzed C−H arylation [15] of chlorinated oligoarylene‐carbazole precursors 4 a – 4 e (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, geometry optimization of the radical-cation intermediate, 13 , could not reach a local energy minimum. 34 These calculations indicate that the formation of an eight-membered ring is favourable in the arenium cation pathway, with a lower energy barrier than for the formation of a six-membered ring. On the other hand, the radical cation pathway does not allow the formation of an eight-membered ring.…”
Section: Resultsmentioning
confidence: 86%
“…[28][29][30][31][32][33][34] Helicenes, the ortho-fused superstructures, have an intrinsic folded spiral superposition of PAHs. 36,37 The topology tailoring in helicenes endows an accessional possibility of stable radical incubation, 34,35,38 circularly polarized luminescence (CPL), 14,39,40 and chiralityinduced spin selectivity (CISS). 41,42 The traditional carbon [n]helicenes with high diradical character and dynamic luminescence switchability is hardly accessible due to resonance delocalization and monotonous electron transfer inherency (e.g.…”
Section: Introductionmentioning
confidence: 99%